2012
DOI: 10.1044/0161-1461(2011/10-0064)
|View full text |Cite
|
Sign up to set email alerts
|

Preliteracy Speech Sound Production Skill and Later Literacy Outcomes: A Study Using the Templin Archive

Abstract: Speech sound disorders appear to be an overt manifestation of a complex interaction among variables influencing literacy skills, including nonlanguage cognition, vocabulary, letter knowledge, and phonological awareness. These interrelationships hold across the range of speech sound production skill, as children with superior speech sound production skill experience superior literacy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
3
27
0
1
Order By: Relevance
“…A recent study by Overby, Trainin, Smit, Bernthal, and Nelson (2012) reported that phonological awareness skills mediated the effects of poor kindergarten speech sound production on reading and spelling skills in first grade, second grade, and third grade, yet vocabulary skills did not account for any of the variance. Although the SSD-only group did not differ significantly from the TL group on the CTOPP Elision subtest, the mean score was lower for the SSD-only group.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study by Overby, Trainin, Smit, Bernthal, and Nelson (2012) reported that phonological awareness skills mediated the effects of poor kindergarten speech sound production on reading and spelling skills in first grade, second grade, and third grade, yet vocabulary skills did not account for any of the variance. Although the SSD-only group did not differ significantly from the TL group on the CTOPP Elision subtest, the mean score was lower for the SSD-only group.…”
Section: Discussionmentioning
confidence: 93%
“…Equally, further investigations are required to examine whether positive long-term language and literacy outcomes previously reported to be associated with age-appropriate consonant cluster acquisition (Overby et al, 2012) do indeed eventuate. The ongoing detailed analysis and monitoring of speech and language progress of larger cohorts of children, who receive optimized amplifi cation and/or cochlear implants in their fi rst year of life within particular early intervention service models, will be important for informing our evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…Third, consonant clusters dominate word-fi nal position (e.g., last /last/; jump / ʤ ʌ mp/) (Locke, 1983) and are particularly important for marking phone tically complex morphophonemes -grammatical morphemes realized by consonant clusters, such as the non-fi nite plural (e.g., boats /bo ʊ ts/) and possessive (e.g., dog ' s /d ɒ ɡ z/) morphemes, as well as fi nite third person present singular (e.g., eats /its/) and past tense (e.g., asked /askt/) morphemes (Paul & Shriberg, 1982). Fourth, the accurate use of consonant clusters has been associated with improved expressive language outcomes (particularly given their role in marking grammatical morphophonemes) and overall long-term superior literacy development (Overby, Trainin, Smit, Bernthal, & Nelson, 2012). Fifth, diffi culty with the production of consonant clusters (e.g., reduction of clusters from two or three elements to one, such as star /sta/ realized as [ta]) is common in pre-school-aged children with speech sound disorder (Hodson & Paden, 1981).…”
Section: Consonant Clusters -Why Are They Important To Investigate?mentioning
confidence: 99%
“…Although PA, reading, and spelling deficits are more common in children with co-occurring language impairments, several studies report that even children with SSDs who have typical language skills are at elevated risk for PA and reading problems (Bird et al, 1995; Overby, Trainin, Smit, Bernthal, & Nelson, 2012; Raitano et al, 2004; Rvachew et al, 2003). Moreover, recent functional magnetic resonance imaging results demonstrate that school-age children with residual speech sound errors show an array of cortical and subcortical differences in how they process phonological information in both spoken and written language (Preston, et al, 2012).…”
Section: Phonological Representations Phonological Awareness and Spmentioning
confidence: 99%